Remote PC Wake-On Design Manufacture in Mujahidin Mosque at Candi Mendut - Rizki Priya Pratama (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2021)
There are several methods to turn on a PC from other places, one of which is WOL (wake-on lan). This method requires modem configuration to enable WOL and port forwarding features. However, if it is not possible, there is one method offered by the researcher. The method is creating a system that functions to turn on the PC via the MQTT protocol. This system consists of electronic devices and android applications. Both can be connected to the internet network. The function of this device is to connect the PWRBTN and GND pins for 0.3 seconds. While the android application